The impact of mergers and acquisitions announcement on the short-term stock market performance in the biotechnological and pharmaceutical industry. Empirical evidence from US companies during the period of 2005 to 2017. - Ciarkowski, Maciej (2019)
Transactions of mergers and acquisitions have become a common way of the company’s development in the past decades, especially in the biopharma industry – only in 2019, there were 936 announced transactions. However, there are few studies that comprehensively examine these sectors and their impact on the shareholders’ wealth. Using a sample of 136 mergers and acquisitions announcements during the period 2005-2017 and employing the event study methodology, we examine a short-term impact on the US acquirers in the pharmaceutical and biotechnological industry. In order to better understand the M&A effect, we have distinguished five factors that may have an impact on the stock movements: cross-border/domestic transactions, method of consideration, industry, previous M&A experience and the deal size. Overall, our findings indicate that M&A announcements have a significant and positive impact on stock performance. However, when it comes to the other factors, we found that cross-border deals experienced a negative effect on the stock performance during the pre-announcement period and positive after and on the announcement day. Methods of payment based on cash only, generate mostly positive returns, while stock and mixed offers show harmful effects. Similarly, transactions announced by pharmaceutical enterprises induce favourable effects on the stock market performance, in comparison to biotechnological ones. Previous M&A experience resulted in positive and significant abnormal returns only in the post-announcement windows, while findings from the transaction size factor cannot designate the impact on the shareholders’ wealth.